2018
DOI: 10.1080/2162402x.2018.1512943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PD-L2, B7-H3 and CTLA-4 immune checkpoint proteins in genetic subtypes of meningioma

Abstract: Meningioma is the most common brain tumor in adults. Surgical resection remains the primary treatment. No chemotherapy exists. However, gene mutations now could explain~80% of meningioma and targeted therapies based on these are being investigated. Furthermore, with the recent discovery of PD-L1 in malignant meningioma, clinical trials using immunotherapy have commenced. Here, we report for the first time the expression profiles of immune checkpoint proteins PD-L2, B7-H3 and CTLA-4 in meningioma and their asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 55 publications
1
51
0
Order By: Relevance
“…For example, meningiomas commonly have isolated monosomy 22/del(22q) mutations, which show increased tumor-infiltrating M1-subtype macrophages, NK cells, and T-cells ( 41 , 42 ). Another important aspect of genetic alterations in meningiomas is that molecular subtypes characterized by specific genetic mutations express different checkpoint molecules ( 34 , 43 ). It is conceivable that by molecularly classifying meningiomas to determine the presence of different mutations, chromosomal derangements, and their relationship to immune cell infiltration, we will be able to determine optimal immunotherapeutic strategies for patients.…”
Section: Genetic Alterations Of Meningiomasmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, meningiomas commonly have isolated monosomy 22/del(22q) mutations, which show increased tumor-infiltrating M1-subtype macrophages, NK cells, and T-cells ( 41 , 42 ). Another important aspect of genetic alterations in meningiomas is that molecular subtypes characterized by specific genetic mutations express different checkpoint molecules ( 34 , 43 ). It is conceivable that by molecularly classifying meningiomas to determine the presence of different mutations, chromosomal derangements, and their relationship to immune cell infiltration, we will be able to determine optimal immunotherapeutic strategies for patients.…”
Section: Genetic Alterations Of Meningiomasmentioning
confidence: 99%
“…Several recent studies have aimed to characterize the interactions between meningiomas and the immune system. Specifically, studies of the immune microenvironment in meningiomas have revealed that checkpoint molecules like NY-ESO-1, PD-L1, PD-L2, B7-H3, and CTLA-4 are expressed in meningiomas and may be at least partly responsible for the suppression of the anti-tumor immune response ( 43 , 78 81 ). Programmed Death Ligand-1 (PD-L1) is expressed in meningiomas, and expression levels are higher for higher-grade tumors ( 80 ).…”
Section: Immunotherapeutic Strategies For High Grade Meningiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Proctor et al [51] also recently linked mutations in the PI3K/AKT/mTOR pathway to elevated levels of the immune checkpoint proteins PD-L2 and B7-H3, strengthening the evidence that genetic changes can stimulate a different tumour microenvironment. The impact of somatic alternations on immune responses has previously been shown in BRAF mutations in melanoma [54] and IDH mutations in glioma [55].…”
Section: Discussionmentioning
confidence: 88%
“…The immune checkpoint marker PD-L1 has been shown to increase in anaplastic meningiomas [49], suggesting that higher-grade tumours harbour a more immunosuppressive tumour microenvironment [50], although immune therapy targeting PD-L1 in meningiomas may be limited due to expression levels [51,52]. Recently, lower proportions of PD-1 positive cytotoxic T cells (CD3 + CD8 + FOXP3 − ) have been associated with poorer survival, with longitudinal analyses of the tumour-infiltrating T-lymphocytes suggesting large changes in the microenvironment over the course of the disease [25].…”
Section: Discussionmentioning
confidence: 99%